N-terminal pro-brain natriuretic peptide is related with coronary flow velocity reserve and diastolic dysfunction in patients with asymmetric hypertrophic cardiomyopathy. Issue 4 (October 2017) - Tesic, Milorad; Seferovic, Jelena; Trifunovic, Danijela; Djordjevic-Dikic, Ana; Giga, Vojislav; Jovanovic, Ivana; Petrovic, Olga; Marinkovic, Jelena; Stankovic, Sanja; Stepanovic, Jelena; Ristic, Arsen; Petrovic, Milan; et al.
Abstract: Background: The relations of elevated N-terminal pro-brain natriuretic peptide (NT-pro-BNP) and cardiac ischemia in hypertrophic cardiomyopathy (HCM) patients is uncertain. Therefore we designed the study with the following aims: (1) to analyze plasma concentrations of NT-pro-BNP in various subsets of HCM patients; (2) to reveal the correlations of NT-pro-BNP, myocardial ischemia, and diastolic dysfunction; (3) to assess predictors of the elevated plasma levels of NT-pro-BNP. Methods and results: In 61 patients (mean age 48.9 ± 16.3 years; 26 male) with asymmetric HCM plasma levels of NT-pro-BNP were obtained. Standard transthoracic examination, tissue Doppler echocardiography with measurement of transthoracic coronary flow velocity reserve (CFVR) in left anterior descending artery (LAD) was done. Mean natural logarithm value of NT-pro-BNP was 7.11 ± 0.95 pg/ml [median value 1133 (interquartile range 561–2442) pg/ml]. NT-pro-BNP was significantly higher in patients with higher NYHA class, in obstructive HCM, more severe mitral regurgitation, increased left atrial volume index (LAVI), presence of calcified mitral annulus, elevated left ventricular (LV) filling pressure and in decreased CFVR. Levels of NT-pro-BNP significantly correlated with the ratio of E/e′ ( r  = 0.534, p  < 0.001), LV outflow tract gradient ( r  = 0.503, p  = 0.024), LAVI ( r  = 0.443, p  < 0.001), while inversely correlated with CFVR LAD ( r  = −0.569, p  < 0.001). When multivariate analysis was done only CFVR LAD and E/e′ emerged as independent predictors of NT-pro-BNP. Conclusion: Plasma levels of NT-pro-BNP were significantly higher in HCM patients with more advanced disease. Elevated NT-pro-BNP not only reflects the diastolic impairment of the LV, but it might also be the result of cardiac ischemia in patients with HCM.